ANALISIS PERBANDINGAN KINERJA DENGAN BALANCED SCORECARD PADA KSU BERINGKIT DENGAN KSU DENBANTAS - Rahayu, Nyoman Etia; Wirajaya, I Gede Ary (E-Jurnal Akuntansi, 2014)
This research aimed to determine performance of KSU Beringkit and KSU Denbantas using Balanced Scorecard approach. Research at KSU Beringkit and KSU Denbantas choosed because both cooperatives have many business units in addition, not only to savings and loans. Therefore, performance of both cooperatives can be assessed more accurately because not only assess level of user satisfaction of services transactions between members of savings and credit in cooperatives but also the outside members of cooperative who make transactions in other business units. It causes both cooperatives have advantages than other types of cooperatives and more accurately to research.
Keywords: balanced scorecard, penilaian, perbandingan, kinerja